Class conflict in Victorian fiction with especial Reference to Hardy’s novels - Dr Saima Manzoor; Ghulam Rasool; Shumaila Barozai (Al-Burz, 2019)
The Victorian novel is dominated by class conflict. This research paper is an attempt to define the different classes of the society and the attitude of the Victorian novelists, especially, that of Hardy’s, towards class distinction. The present study includes the nineteenth century novelists, namely, Charles Dickens, George Eliot, Charles Kingsley, George Meredith and Thomas Hardy who in their works focus upon class conflict. The paper, while highlighting the attitude of the Victorian writers towards class conflict, mainly explores the major novels of Hardy who, being highly conscious about his humble origin, presents such characters who are inclined to social improvement. In Victorian fiction the elite class is marked with meanness and moral degradation. The research study would provide relevant information about the conflict between haves and have not especially with reference to Hardy’s fiction.